Characterizing the in vitro and in vivo effect of bicarbonate on azithromycin activity against Acinetobacter baumannii - Hadley Jaramillo; Matthew Slarve; Derek Long; Michelle Zorawik; Kristine Goy; Lauren Popel; Rosemary She; Brad Spellberg; Brian Luna (PLoS ONE, 2026)
Carbapenem-resistant Acinetobacter baumannii (CRAB), a Gram-negative bacterial pathogen, has been identified by Centers for Disease Control (CDC) as the top priority pathogen for which new antibiotics are needed. We found that the addition of bicarbonate at physiologically normal levels found in the blood (23.8 mM) increased susceptibility of A. baumannii clinical isolates (n = 63) to azithromycin and resulted in MIC50 shift from 64 mg/L in CAMHB to 1–2 mg/L in CAMHB + bicarbonate (23.8 mM) or RPMI-1640 respectively. To characterize in vivo efficacy in murine blood and lung infection models, mice were infected with A. baumannii and then mice were treated with a human equivalent dosing strategy of azithromycin. In vivo outcomes greatly depended on the infection model used. The bloodstream infection model showed a statistically significant increase in survival of the treatment group compared to the control group. However, that was not found with the oral aspiration infection model. We hypothesize that these in vivo results are due to the local differences of bicarbonate concentrations at the site of infection throughout the course of infection.